Predicting Soil Nitrogen Availability for Maize Production in Brazil - Braos, Lucas Boscov [UNESP]; Carlos, Roberta Souto [UNESP]; Kuhnen, Fernando; Ferreira, Manoel Evaristo [UNESP]; Mulvaney, Richard Lesley; Khan, Saeed Ahmad; Cruz, Mara Cristina Pessôa da [UNESP] (MDPI, 2022)
Maize (Zea mays L.) is a crop widely cultivated in the state of São Paulo, and the sustainable management of nitrogen (N) nutrition is crucial to improving productivity and the environment, which calls for a reliable means of predicting potentially available soil N. A study was undertaken to evaluate and compare biological and chemical indices of potential N availability for a diverse set of 17 soils collected in the northwest region of São Paulo state. For this purpose, mineralization assays were performed at three distinct temperatures, and chemical assessments were carried out using the Illinois Soil Nitrogen Test (ISNT) and by fractionation of hydrolysable soil N. In addition, a greenhouse experiment was conducted to determine dry matter and N accumulation in the aboveground parts of maize plants. Potentially available N estimated by the incubation methods increased with increasing temperature and was strongly correlated with N uptake (r = 0.90). Hydrolysable N fractions varied widely among the soils studied and were more variable for amino sugar N than for other fractions. Potentially available N estimated by the ISNT was highly correlated with hydrolysable amino acid N and amino sugar N (r = 0.95–0.96) and also with plant dry matter accumulation (r = 0.82) and N uptake (r = 0.93). The ISNT has potential to improve fertilizer N recommendations for maize production in Brazil, provided that the test values are interpreted relative to an appropriate calibration database, planting density, and other factors affecting crop N requirement.
Keywords: aerobic incubation; Illinois Soil Nitrogen Test (ISNT); mineralization; soil N fractionation